Anti-oxidative, acetylcholinesterase and pancreatic lipase inhibitory activities of compounds from Dasiphora fruticosa, Myricaria alopecuroides and Sedum hybridum - G, Odontuya (Mongolian Journal of Chemistry, 2017)
Total of 35 phenolics and flavonols were isolated from flowers and leaves of Dasiphora fruticosa Rydb., from branches of Myricaria alopecuroides Schrenk. and from the herb of Sedum hybridum L. The isolated compounds were identified on the basis of spectral data and tested for their anti-oxidative, acetylcholinesterase and pancreatic lipase inhibitory activities.Quercetin glycosides, gallic acid, (-)EGCG and gossypetin-8-O-xylopyranoside tellimagrandin II exhibited strong anti-oxidative activity by the DPPH scavenging method. The acetylcholinesterase inhibitory activity of quercetin glycosides and (-)EGCG was higher than those of other compounds. Whereas, tellimagrandin II, (-)EGCG and gallic acid derivatives exhibited the most potent inhibitory activity against the pancreatic lipase enzyme among the isolated compounds. Only (-)EGCG showed a prominent activity against all assayed experiments. It was concluded that these plants could be studied further for their potential as anti-oxidative, anti-aging and lipid lowering active products.